Neuroanatomy of lumbosacral and pudendal plexus in pigeon of Bangladesh - Alam, J; Hasan, MK (Bangladesh Journal of Animal Science, 2023)
The present study aims to reveal the neuroanatomy of the lumbosacral and pudendal plexus in pigeons of Bangladesh. Six adult male domesticated pigeons were used in this study. The body cavities of the pigeons were opened after the administration of the anesthetics. The nerve roots of the plexus were dissected separately and photographed. We found that the lumbosacral plexus consisted of the lumbar plexus and the sacral plexus. The lumbar plexus was formed by the union of the ventral branches of the first, second, and third lumbar (L1-L3) spinal nerves. The lumbar plexus was branched into cutaneous femoris nerve, coxalis cranialis nerve, femoralis nerve, saphenous nerve, and obturatorius nerve. The sacral plexus was formed by the union of the ventral branches of the fourth lumbar and first, second, third, and fourth sacro-coccygeal spinal nerves. The sacral plexus gives off a large sciatic nerve and innervated as tibial and fibular nerve into musculature of the hind limb of the pigeon. The pudendal plexus was organized from the fourth, fifth, sixth and seventh sacro-coccygeal spinal nerves and were innervated into the tail region of the domesticated pigeons. This study was the first investigation of lumbosacral and pudendal plexus in domesticated pigeons and the results may serve as a basis for further investigation in other species. Bangladesh Journal of Animal Science 52 (4): 98-104